Perancangan Enterprise architecture Menggunakan Metode TOGAF ADM (Studi Kasus pada PT RMM) - Mohamad Afif (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Information technology (IT) development in a company is often not based on good design on future development scenarios, technology development requirements, and information system. Information technology that has been built also inefficient according to company's vission and mission. Enterprise Architecture was built as a corporate master plan that became a reference or guidance in information technology development. Enterprise Architecture is an information technology company coming from the provision of needs and information embodied in form of application systems and provision of technology infrastructure. Architectural overview provides important values for company where management can develop more effective strategies in monitoring business processes and technological infrastructure. TOGAF provides detailed-methods of how to build, manage, and implement enterprise architecture and information systems called Architecture Development Method. This method contains some activities used in modeling the development of company's architecture. It is also a guide for planing, designing, developing, and implementing information systems architecture for organizations. The result of this design is an information technology architecture that becomes the guide for management in determining the budget of IT needs based on priority scale to support the efficiency of the company.